State Wise Modeling and Descriptive Analytics with Data Visualization of Indian Southern Power Grid Operation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The energy grid storage is a collection of methods used to store large-scale electrical energy within an electric grid. Data visualization alludes to the procedures used to data or information by encoding it as visual plans. The goal is to pass on information obviously and gainfully to customers. It involves producing images that impart connections among the represented data to viewers of the images. Data visualization design toolkits help clients to investigate information and make representations. In this paper, we present data visualization design for demand data based on state wise of Demand Met, Day Energy Forecast and Deviation particulars over day wise and week wise of southern regional grid for various states is proposed. The performance measure of state wise outcome is determined by visualizing its demand needs over its state energy consumption where tamilnadu leads its maximum energy needs compared with other states.